Sand-Lime Column Stabilization On The Consolidation Of Soft Clay Soil - Merdhiyanto, Puguh, Anto Budi Listyawan, S.T, M.Sc, Agus Susanto, S.T, M.T (2015)
The area in Indonesia has many kind of soft clay, can be found in Central Java area includes Blora, Purwodadi, Solo, Sragen, Klaten and Yogyakarta. It exposes a problem when building on soft clay sites. Therefore to improve infrastructure, many construction activities are increasingly focused on the behavior of the soil. Especially with different soil conditions not always the same in each area of construction that requires accuracy in the planning and execution of construction itself. To overcome the soil conditions are not as expected, then there are several techniques used in order to improve the quality of a particular soil, among which are add other materials (lime) and the vertical drain technique. This research aims to determine the effect of sand-lime column stabilization on soft clay soil from Troketon Pedan Klaten in terms of the consolidation coefficient (Cv), compression index (Cc), and the settlement consolidation (Sc) along with some physical properties. Spacing sampling variation is 50 cm; 33.33 cm and 16.67 cm from sand-lime column. The results physical properties show, from spacing sampling variation of the sand-lime column that specific gravity (Gs) and liquid limit (LL) values decreased, whereas the plastic limit (PL) and shrinkage limit (SL) values actually increased, whereas plasticity index (PI) decreased when the closer spacing sampling of sand-lime column. From the test mechanical properties results show, the closer the sampling of the sand-lime column Cv value tends to increase, the highest average Cv values are 0.00177 cm2/s occur in soil samples 16.67 cm from sand-lime column. While the value of compression index (Cc) tends to decrease, the Cc value was smallest are 0.655 occur in the soil samples using a sand-lime column at a spacing sampling 16.67 cm. While settlement consolidation (Sc) decreases, the smallest Sc value are 0.245 cm occurs in soil samples with sand-lime column at a spacing of 16.67 cm. Based on the above study showed that the addition of sand-lime column can increase/improve the physical properties and mechanical properties of soft clay from Troketon Pedan Klaten.